2016
DOI: 10.1155/2016/6874207
|View full text |Cite
|
Sign up to set email alerts
|

Xyloglucan for the Treatment of Acute Gastroenteritis in Children: Results of a Randomized, Controlled, Clinical Trial

Abstract: Background. Xyloglucan, a film-forming agent, improves intestinal mucosa resistance to pathologic damage. The efficacy, safety, and time of onset of the antidiarrheal effect of xyloglucan were assessed in children with acute gastroenteritis receiving oral rehydration solution (ORS). Methods. This randomized, controlled, open-label, parallel-group, multicenter, clinical trial included children (3 months–12 years) with acute gastroenteritis of infectious origin. Children were randomized to xyloglucan and ORS, or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 12 publications
1
41
0
Order By: Relevance
“…4,16,[23][24][25][26][27] In our study, for the first time, we have demonstrated that the combination of a mixture of oligoand polysaccharides and a reticulated protein is a safe and feasible treatment to reduce main symptoms and to improve QoL in patients with IBS. Both ingredients are not absorbed, their effect local on the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…4,16,[23][24][25][26][27] In our study, for the first time, we have demonstrated that the combination of a mixture of oligoand polysaccharides and a reticulated protein is a safe and feasible treatment to reduce main symptoms and to improve QoL in patients with IBS. Both ingredients are not absorbed, their effect local on the intestinal mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…The plasmatic peak is between 2 and 6 h after ingestion -the half-life is from 2 to 57 h . In about 5 days, more than 90% of ∆-9-tetrahydrocanabinol (THC) is excreted from the body [14].…”
Section: Exogenous Cannabinoids -Absorptionmentioning
confidence: 99%
“…To date, the beststudied substances include xyloglucan (a hemicellulose polysaccharide found in all land plants) and gelatin tannate (a complex of tannic acid, which possesses astringent, antibacterial, and anti-inflammatory properties, and is a protective gelatin). However, data on the efficacy of these two agents are very preliminary [10][11][12][13].…”
Section: Mucosal Protective Agentsmentioning
confidence: 99%